Perspectives and awareness of endoscopy healthcare professionals on sustainable practices in gastrointestinal endoscopy: results of the LEAFGREEN survey - Cunha Neves, João A.; Rodriguez de Santiago, Enrique; Pohl, Heiko; Lorenzo-Zúñiga, Vicente; Cunha, Miguel F.; Voiosu, Andrei M.; Römmele, Christoph; Penman, Douglas G.; Albéniz, Eduardo; Siau, Keith; Donnelly, Leigh; Elli, Luca; Pioche, Mathieu; Beilenhoff, Ulrike; Arvanitakis, Marianna; Weusten, Bas L.A.M.; Bisschops, Raf; Hassan, Cesare; Messmann, Helmut; Gralnek, Ian M.; Dinis-Ribeiro, Mário (Endoscopy, 2024)
Background Gastrointestinal (GI) endoscopy is one of healthcare’s main contributors to climate change. We aimed to assess healthcare professionals’ attitudes and the perceived barriers to implementation of sustainable GI endoscopy.Methods The LEAFGREEN web-based survey was a cross-sectional study conducted by the European Society of Gastrointestinal Endoscopy (ESGE) Green Endoscopy Working Group. The questionnaire comprised 39 questions divided into five sections (respondent demographics; climate change and sustainability beliefs; waste and resource management; single-use endoscopes and accessories; education and research). The survey was available via email to all active members of the ESGE and the European Society of Gastroenterology and Endoscopy Nurses and Associates (ESGENA) in March 2023.Results 407 respondents participated in the survey (11% response rate). Most participants (86%) agreed climate change is real and anthropogenic, but one-third did not consider GI endoscopy to be a significant contributor to climate change. Improvement in the appropriateness of endoscopic procedures (41%) and reduction in single-use accessories (34%) were considered the most important strategies to reduce the environmental impact of GI endoscopy. Respondents deemed lack of institutional support and knowledge from staff to be the main barriers to sustainable endoscopy. Strategies to reduce unnecessary GI endoscopic procedures and comparative studies of single-use versus reusable accessories were identified as research priorities.Conclusions In this survey, ESGE and ESGENA members acknowledge climate change as a major threat to humanity. Further improvement in sustainability beliefs and professional attitudes, reduction in inappropriate GI endoscopy, and rational use of single-use accessories and endoscopes are critically required.